The Effect of the Process-Oriented Guided Inquiry Learning Model on Students' Problem-Solving Skills in the First Law of Thermodynamics - Karina Nur Ilma; Rifa’atul Maulidah; Ernita Susanti (Postgraduate, University of Mataram, 2024)
This study aimed to examine the effect of the Process-Oriented Guided Inquiry Learning (POGIL) model on students' problem-solving skills in the topic of the first law of thermodynamics. The research was motivated by pre-study findings showing students' struggles in identifying problems and applying solutions, partly due to limited stimulation in developing critical thinking and inquiry skills. A quasi-experimental method with a nonequivalent control group design was used. The population included 168 Class XI Science students at SMA Negeri 4 Tasikmalaya, with purposive sampling selecting two classes as experimental and control groups. Data were collected using pretests and posttests comprising eight essay questions assessing four stages of problem-solving: identifying problems, planning solutions, implementing solutions, and evaluating results. Hypothesis testing (ttest) at a 95% confidence level showed tcount > ttable (9.78 > 1.67), confirming a significant positive effect of the POGIL model. The findings indicate that the POGIL model effectively enhances students' problem-solving skills, particularly in identifying problems, formulating hypotheses, and analyzing solutions. However, its implementation requires adequate preparation and teacher understanding of its stages. These results suggest that POGIL is a promising approach to fostering critical thinking and problem-solving skills in physics education.